“Itaque Tam Istud Vitandum Habebit Quam Hercule Fugiendum Venandi aut Aucupandi Studium, Quibus Rebus Plurimae Operae Avocantur” - Benincasa, Zuzanna (Studia Historiae Oeconomicae, 2024)
The object of the study consists in legal issues related to hunting wild birds, discussed by Roman classical jurists. The analysis of the sources reveals that the main problem they had to deal with was finding a right balance between the traditional, originating from the ius gentium freedom of hunting with the increasing economic importance of breeding wild birds and, accordingly, the economic interests of rich landowners who tended to reserve the exclusive right for catching wild birds on their lands for themselves. As the consequence of this increasing contrast between the principle of law and the economic reality, wild birds kept in aviaries were deemed to be the property of the owner, as well as those who once tamed were subjected to their control. The jurists also created a concept of animus revertendi which applied to such animals as pigeons and peacocks, whose large-scale breeding involved allowing them to fly away temporarily from the owner. One of the remedies was also ius prohibendi which allowed the owner of the land to prevent entering his land by birders.